The Effect of Academic Procrastination and Learning Motivation on Learning Achievement of English Department Students in Universitas Negeri Padang - M. Renno Rizal; Rusdi Noor Rosa (Universitas Negeri Padang, 2023)
This research was conducted to determine the effect of academic procrastination and learning motivation on the learning achievement of English education students at Padang State University. This type of research is quantitative. The population in this study were students of English Language Education at Padang State University class of 2019 with the sampling technique using proportional random sampling. The number of samples used were 72 student. Data collection techniques used questionnaires and documentation with a Likert scale rating to measure respondents' answers. The data analysis technique uses path analysis with the help of the SPSS version 25 program. The results of this study indicate that (1) academic procrastination influences learning achievement, (2) learning motivation influences learning achievement and (3) academic procrastination and learning motivation influences simultaneously and significant to learning achievement. The implementation of this research is so that English Education students can increase their learning motivation and not take the action of procrastinating doing assignments so that English Education students can improve their learning achievement optimally.Key words: Academic Procrastination, Learning Motivation, and Learning Achievement